MODIFICATION OF URINARY CATHETERS USING ANTIMICROBIALS FROM STREPTOMYCES SP. ABK 07 FOR URINARY TRACT INFECTION RESISTANCE - KINGSLEY, ANGIMA BICHANG’A; R, Usha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main aim of this study is to prevent biofilm formation by impregnating an antimicrobial on urinary catheter. Methods: Catheter segments were immersed in the antimicrobial compound for impregnation. After 2 h, the segments were removed, sterilized and dried after which mechanical and antimicrobial properties of the catheter segments were determined. The shelf life of the impregnated segments was also ascertained as well as anti-biofilm assay. Spectral analysis (UV & FTIR) was also performed. Results: Impregnation was achieved by immersing catheter segments in antimicrobial compound ensuring it does not affect the catheter texture. The impregnated antimicrobial catheters were able to prevent colonization by common uropathogens Escherichia coli, Proteus, Pseudomonas aeruginosa, Staphylococcus aureus, Klebsiella, and Candida albicans for up to 12 weeks. Antibiotic impregnation of the catheters did not affect the mechanical properties and did not render it as unfit for insertion. The antimicrobial-impregnated catheter offers a means of reducing biofilm formation and subsequently reducing the infection in long-term urinary catheter users. Spectral analysis was done by UV-Vis and FTIR. Conclusion: Antibiotic impregnation of the catheters did not affect the mechanical properties and did not render it as unfit for insertion. The antimicrobial impregnated catheter offers a means of reducing biofilm formation and subsequently reducing the infection in long-term urinary catheter users.